Agricultural mechanization status and energy consumption for crop production in Thailand - Anuchit Chamsing; Salokhe, Vilas M.; Singh, Gajendra; Tang, John C.S.; Jayasuriya, H.P.W.; Stout, B. A.; Royal Thai Government (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
The study assessed the situation of agricultural mechanization, energy consumption and cost of production for different farm operations of five major crops viz. rice, maize, sugarcane, cassava and soybean in three regions of Thailand (the Central plain, the North and the Northeast regions). This study was intended to suggest a methodology to formulate an agricultural mechanization plan. Primary data was obtained through field survey and personal interviews using structured questionnaires. The data were collected from 909 farms owned by 487 farmers. Secondary data and energy equivalents were obtained from available literature. The results showed that average,2.0-2.6 persons/family were active in farms. In the study areas, the average planted area for sugarcane production was the largest (4.8-6.9 ha/family) followed by maize (5.2-6.4 ha/family), wet-season soybean (4.1-6.8 ha/family), rainfed rice (3.0-10.5 ha/family), cassava (3.2-4.8 ha/family), irrigated rice (1.4-6 ha/family) and dry season soybean production (2.6-3.2 ha/family) respectively. Over 60% of farmers in the Central plain region growing irrigated rice, rainfed rice and cassava used leased farms. The farmers producing other crops have their own land. More than 90% of farmers in irrigated area, around 60% of farmers growing upland crops in the Central and the Northern regions and less than 50% of farmers in the Northeastern region own agricultural machinery. Less than 10-40% of farmers under study (except about 50% for cassava producers in the Northern and Northeastern regions) used their own machines for custom service. Small and big 4-wheeled tractors were power sources for upland crops with few irrigated areas. The power tillers were used for cultivation of all crops and regions. Use of labor and machinery as well as type and size of machinery varied depending upon crops and regions. The farm operation requirements were depended on cultural practices and machinery available. Mechanization index for the whole kingdom of Thailand was 0.93. Mechanization index for different crops and regions varied from 0.65-0.97. Mechanization index for irrigated rice was maximum followed by those for rainfed rice, maize, wet-season soybean, sugarcane and dry-season soybean respectively. Energy analysis showed that energy input in farm operations for sugarcane production was the highest (14.48-18.65 GJ/ha). For irrigated rice, rainfed rice, maize, wet-season soybean and cassava, it varied between 1.79-18.49, 10.09-13.11, 9.79-12.79, 5.21-10.03 and 4.95-9.13 GJ/ha respectively. Energy input in dryseason soybean production was the lowest. About 62% and 38% of energy inputs in farm operations was from material and physical energy inputs respectively. Energy from fertilizer contributed the highest followed by energy from seed, pesticide and herbicide. Over 97.8 of physical energy input is energy from mechanical power sources. Total energy input for sugarcane in the Central plain was the highest (24.68 GJ/ha), whilst the lowest was energy input for cassava production in the Northeastern region (8.81 GJ/ha). Energy sequester is the main cause of variation of total energy input for different crops. Energy ratio for different crops ranged 2.0-11.1. Both, wet-season and dry-season soybean shows the lowest energy ratio (2.0-3.7) followed by rainfed rice and irrigated rice. Sugarcane give the highest energy ratio (9.3-10.1) followed by cassava and maize. A mechanization plan has been developed.
A dissertation submitted in partial ful{uFB01}llment of the requirements for the degree of Doctor of Engineering in Agricultural Engineering, School of Environment, Resources and Development
Thesis (Ph.D.) - Asian Institute of Technology, 2007
Keywords: Farm mechanization -- Thailand; Crops -- Energy consumption -- Thailand; Agricultural productivity -- Energy consumption -- Thailand